The corset as a fetish object of Victorian England and the crisis of values into the dynamics between class and gender (ModaPalavra e-periódico, 2020)
This article aims to explore the connections between thecorset and fetishism in the nineteenth century and thebeginning of the twentieth century. Supported by theperspective of Anne McClintock on Imperial Leather: Race,Gender and Sexuality in the Colonial Contest (2010), inregards to fetish and the class and gender dynamics, thisarticled analyzed the prominence of the corset in themaintenance of Victorian female domestic idleness. Thescrutiny suggests the crisis of value conducted by theconflict among public and private spaces, by the connectionamong male agency, female stagnation and the impossibilityof pleasure from female idleness are all embodied in thecorset, which converts it into an object of fetishism. Therecovery of the writings of Freud, the study of thegenealogies of fetishism and the resumption of itsetymological origin broadens the meaning of perspectives forthe relation between the corset and the nineteenth centuryfemale body, whose silhouette, drawn by corsetry, delimitedmeasuredly its possibilities in its social role.
Keywords: corset; fetishism; victorian era